Разработка энергоэффективных режимов работы шахтных противоточных известково-обжиговых печей - Форись, С. Н.; Губинский, М. В.; Федоров, С. С.; Федоров, О. Г.; Ковпак, А. Г. (НТУ "ХПИ", 2009)
For reduction of natural gas consumption the working conditions optimization problem of shaft counter-flow lime-kilning furnace is solved. The fuel, air and recycling gas consumptions were examined as controllable working conditions. The furnace-charge with limestone and material burning degree – as independent manufacturing parameters. The expected fuel rate economy made up 17%.
Keywords: энергосбережение; печь; шахтная печь; известково-обжиговая печь